Impact of COVID-19 on clinical trials and clinical research: A systematic review (Nepal Journal of Epidemiology, 2020)
Background: The World Health Organization has reported more than 31,186,000 confirmed cases of coronavirus disease-19 (COVID-19), including 962,343 deaths, worldwide as on September 21, 2020. The current COVID-19 pandemic is affecting clinical research activities in most parts of the world. The focus on developing  a vaccine for SARS-CoV-2 and the treatment of COVID-19 is, in fact, disrupting many upcoming and/or ongoing clinical trials on other diseases around the globe. On March 18, 2020, the United States Food and Drug Administration (FDA) issued an updated guideline for the conduct of clinical trials during the current health emergency situation. The potential challenges, such as social distancing and quarantines, result in study participants’ inaccessibility and trial personnel for in-person scheduled study visits and/or follow-up. Due to the sudden onset and wide-spread impact of COVID-19, its influence on the management of clinical trials and research necessitates urgent attention. Therefore, our systematic review of the literature aims to assess the impact of the COVID-19 pandemic on the conduction of clinical trials and research. The search for the relevant articles for review included the keywords "COVID-19” AND "clinical trial" in PubMed, MEDLINE, Embase, Google scholar and Google electronic databases. Key findings include: delaying subject enrollment and operational gaps in most ongoing clinical trials, which in turn has a negative impact on trial programmes and data integrity. Globally, most sites conducting clinical trials other than COVID-19 are experiencing a delay in timelines and a complete halt of operations in lieu of this pandemic, thus affecting clinical research outcomes.